TV digital na Argentina: a TV como palanque eletrônico - Américo, Marcos [UNESP] (My University, 2012)
The aim of this paper is to describe and analyze the process of implementing the Digital Television in Argentina between November, 2011 and April, 2012, a period where this author has developed postdoctoral research entitled "Digital TV, T-Learning and Edutainment: An Assessment of the Argentine case" at the University of La Matanza in San Justo, City of Buenos Aires, Argentina.

O objetivo deste artigo é descrever e analisar o processo de implantação da TDA Televisión Digital Abierta na Argentina entre novembro de 2011 e abril de 2012, período onde este autor desenvolveu pesquisa de estágio pós-doutoral intitulada TV Digital, T-Learning e Edutretenimento: Uma Avaliação dos Caso Argentino na Universidad de La Matanza em San Justo, Cidade Autônoma de Buenos Aires na República Argentina.
Keywords: Digital television; Digital television in Argentina; Ley de medios; Comunicação Social; TV Digital; Rádio e TV; Produção audiovisual